Universal throttling device - S. V. Dolgov; R. N. Kulesh; V. Yu. Polovnikov; S. E. Shalygin (Известия Томского политехнического университета: Инжиниринг георесурсов, 2009)
The paper introduces the description of a new regulated throttle orifice design, the laboratory bench to study its characteristics and the results of experimental determination of the orifice hydraulic resistance coefficients. The authors have made the valid conclusion on the prospects of applying the device to adjust liquid or gas flow in different systems due to the comparative simplicity of its design and essential cheapness compared with the existing analogues. The need of future experiments on the regulated throttle orifice in a wide range of geometric characteristics and fluid flow to identify the boundaries of possible application of the device in a variety of industries was noted.